Strategi pengurusan untuk mengkomersialkan buku sastera kanak-kanak - Nor Atikah, binti Shahdan (Universiti Malaysia Sarawak (UNIMAS), 2015)
This study to see Management Strategies For Commercialising of Children’s Literature Book. Data were collected through interviews. The objective of the study is to examine how the content of children's literature books such as books design, pictures, writing style, the art of illustration and type of paper. Reviewing management of book publishing children's literature, also in terms of financial cost and market promotion. Analyze how writers write or compose a book of children's literature corner writing management. The study finding that writers produce more books in English than in Malay. The publisher and the artist should jointly promote and market the books so that communities, especially parents aware and focused on the reader's literary books to their children. It was found that parents who would encourage children to read books in English literature. This resulted in children less aware of Malay literature. The inspiration of this study was fighting for A.Samad Said National Laureate field.